2005
DOI: 10.1083/jcb.200407070
|View full text |Cite
|
Sign up to set email alerts
|

BACE overexpression alters the subcellular processing of APP and inhibits Aβ deposition in vivo

Abstract: Introducing mutations within the amyloid precursor protein (APP) that affect β- and γ-secretase cleavages results in amyloid plaque formation in vivo. However, the relationship between β-amyloid deposition and the subcellular site of Aβ production is unknown. To determine the effect of increasing β-secretase (BACE) activity on Aβ deposition, we generated transgenic mice overexpressing human BACE. Although modest overexpression enhanced amyloid deposition, high BACE overexpression inhibited amyloid formation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
127
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(144 citation statements)
references
References 47 publications
15
127
1
1
Order By: Relevance
“…Overexpression of BACE1 decreases the level of mature APP by disturbing axonal transport in the brain in vivo (36); however, based on our observations in undifferentiated N2a cells (Fig. 5A), it is reasonable to speculate that the decrease in the level of mature hAPP is due to proteolysis by overexpressed BACE1 along with elevated generation of CTF␤/ C99 and CTF␤Ј/C89.…”
Section: Elevated Bace1 Activity Cleaves Ctf␤/c99 the Precursor Of Amentioning
confidence: 40%
See 3 more Smart Citations
“…Overexpression of BACE1 decreases the level of mature APP by disturbing axonal transport in the brain in vivo (36); however, based on our observations in undifferentiated N2a cells (Fig. 5A), it is reasonable to speculate that the decrease in the level of mature hAPP is due to proteolysis by overexpressed BACE1 along with elevated generation of CTF␤/ C99 and CTF␤Ј/C89.…”
Section: Elevated Bace1 Activity Cleaves Ctf␤/c99 the Precursor Of Amentioning
confidence: 40%
“…Third, we demonstrated that elevation of BACE1 activity due to overexpression of the enzyme results in secondary cleavage of CTF␤/C99 at the ␤Ј-site, dramatically increasing A␤(11-XX) production. This is true, at least in the cell study, even for APP harboring the Swedish mutation, which predominantly produces A␤(1-XX), although a pilot study in a BACE-overexpressing transgenic mouse suggested that reduction in A␤ deposition is mediated by another mechanism (36). Finally, we showed that A␤(11-XX) may be more metabolically labile than A␤(1-XX) in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Short pulse labeling with [ 35 S]Met/Cys showed that wtAPP expression is similar in the stable pools analyzed (data not shown). Continuous labeling for 3 h showed a marked reduction in the levels of mature APP in stable cells overexpressing wtBACE1, indicative of efficient processing by BACE1, as observed in previous studies (61). To confirm this notion, we examined the proteolytic products derived from BACE1 cleavage of APP, i.e.…”
Section: Bace1 Is S-palmitoylated At 4 Cysteine Residues-previ-mentioning
confidence: 87%